Multi-stimuli-responsive fluorescence of a highly emissive difluoroboron complex in both solution and solid states. Issue 9 (9th February 2017) - Fang, Wenyan; Zhang, Yuyang; Zhang, Gaobin; Kong, Lin; Yang, Longmei; Yang, Jiaxiang
Abstract : A difluoroboron complex (TC ) with high fluorescence quantum yields both in solution and in the solid state has been synthesized. The colors and fluorescence emission ofTC can be switched by grinding and acids/bases. It can be used for multi-stimuli-responsive fluorescent probes. Abstract : A highly fluorescent emissive difluoroboron complex (TC ) was designed, synthesized and characterized. The absolute fluorescence quantum yields ofTC are 33.0% in the solid state and 26.0% in the solution state. The results of X-ray diffraction analysis demonstrate that the rigid structure, the intermolecular hydrogen bonding and the well-ordered as well as loose molecular packing are the major reasons for the high fluorescence emission. Moreover, the colors and fluorescence emission ofTC can be switched by external stimuli including grinding and acids/bases. Powder X-ray diffraction (PXRD) investigation verifies that the crystalline–amorphous state transformation between the original and ground states might be attributed to the mechanochromic luminescence properties. The high fluorescence emission and multi-stimuli-responsive fluorescence properties reveal thatTC can be used as rewritable information storage, security ink and a fluorescence indicator for acids/bases.